Literature review of installation logistics for floating offshore wind turbines - Jürgen Weigell; Carlos Jahn (Adapting to the Future: Maritime and City Logistics in the Context of Digitalization and Sustainability. Proceedings of the Hamburg International Conference of Logistics (HICL), Vol. 32, 2021)
Purpose: Currently floating offshore wind emerges as a new technology and thus making offshore windfarms in areas feasible where it was due to certain conditions (water depths, soil conditions) not feasible to install fixed offshore wind turbines. The installation process of floating offshore wind foundations is very different from fixed foundations and thus results in new installation processes. Methodology: In this literature review papers over the last ten years with focus on floating offshore installation logistics will be identified and sorted by relevance, year of publication and quality. The publications will also be grouped into the different foundation types Semi-floater, Spar buoy and Tension-leg. These groups will be subdivided further into costs, technical or processes related to logistics. Findings: The paper will show an overview of current processes and trends in installation logistics for floating offshore wind turbines. Currently the existing reviews lack for example scientific papers and supply chain requirements (Carbon Trust, 2015) or they are focused only on technical issues (Wang, et al., 2010). Originality: This paper is original in the sense that currently no complete, thorough and up-to-date literature review for the installation logistics and the supply chain of floating offshore wind exists.
urn:nbn:de:gbv:830-882.0162417; hdl:10419/249609; https://econpapers.repec.org/RePEc:zbw:hiclpr:32
Keywords: 650; Sustainability